Peran Komunitas Islam dalam Menyemangati Keagamaan para Pemuda - Istiqomah Bekthi Utami; Agus Ahmad Safei (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
This study aims to find out how the work program, the constraints, the role, the success rate, and the implementation of the program conducted by Pesantren Yatim Al-Hilal in empowering orphaned resources by building the community's caring participation for abandoned orphans. Place research conducted by the author that is in Pesantren Yatim Al-Hilal Village Rancapanggung Kec. Cililin Kab. West Bandung. The method used in this research is descriptive method. Based on the results of research conducted on this Pesantren Yatim Al-Hilal, the authors found out that empowerment of orphans conducted by Al-Hilal pesantren by providing human resource development by improving both social and religious knowledge, by meeting the needs of life for orphans as the realization of the success of orphans in achieving their goals and can be useful for the nation, and the country.